Brand equity measurements and service delivery: Empirical study from the Nigerian insurance industry - Sunday Stephen Ajemunigbohun; Sunday Adekunle Aduloju (Economic and Environmental Studies (E&ES), 2017)
This study evaluates brand equity measurements on service delivery of insurance companies in Nigeria. An explanatory research design was employed. A purposive sampling technique was adopted. Structured questionnaire was employed for data gathering exercise. The study surveyed 31 insurance companies in Nigeria; with a sample size of 212 giving a response rate of 68%. More so, data collected was analysed using multiple regression method. Findings from the study have shown the relative importance of individual brand equity measurement and how positively related to service delivery of insurance companies in Nigeria. This research awakes the regulatory body of the need to continually engage academia, insurance practitioners and other stakeholders in scrutinising and improving insurance market penetration level in Nigeria. Insurance practitioners are enjoined to take value creation in their service delivery process critically important in a bid to allow for good brand repute and image. Lastly, National Insurance Commission should take its supervisory function crucial by regularly engaging in getting feedbacks from insuring populace concerning customers' insurance brand judgment. The study provides an empirical approach to managers of insurance companies
Keywords: D23; M02; Y09; 330; Brand equity; service delivery; brand trust; Insurance companies; Nigeria